Procesne (ne)ovire pri odločanju za mediacijo v gospodarskih sporih - Pogorelčnik Vogrinc, Neža (Podjetje in delo, 2025)
Given that only a small proportion of parties in court proceedings in Slovenia opt for mediation, they clearly consider alternative dispute resolution to be less reliable than court proceedings. Although in theory there are many arguments in favour of mediation (the process is faster, normally cheaper, the relationship between the parties improves even if no agreement is reached, and if an agreement is reached, the parties are satisfied with the solution, which makes its enforcement voluntary), these are clearly not convincing enough in practice. One can only speculate about the main concerns that lead parties to resist mediation, but some of them are undoubtedly of a legal nature. This article addresses the most common legal questions faced by creditors having a mediation as an option for resolving their dispute. Firstly, it addresses the concern that the time spent on mediation will cause the limitation period to expire; secondly, the situations where a party to mediation finds itself in insolvency proceedings; and thirdly, the situations where an interim order has been issued against the debtor. Finally, the article addresses the question of how the commencement or progress of legal proceedings affects mediation, or how the commencement or progress of mediation affects (pending) legal proceedings. By explaining and clarifying the above (legal) issues, the article familiarizes creditors with the mediation process and assures them that any fears about this method of dispute resolution are unfounded.